2018
DOI: 10.18632/aging.101465
|View full text |Cite
|
Sign up to set email alerts
|

Age-related M1/M2 phenotype changes in circulating monocytes from healthy/unhealthy individuals

Abstract: Macrophage polarization is a candidate biomarker of disease-related inflammatory status, but its modulation during aging has not been investigated. To do this, the M1/M2 profile was assessed by CD80/CD163 gating in classical (CD14++CD16-), intermediate (CD14++CD16+), and non-classical (CD14lowCD16+) monocytes from 31 healthy subjects (CTRs) of different ages. Cytofluorimetric analysis showed a significantly different CD80/CD163 distribution in the three subsets, as more than 80% of classical and intermediate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 36 publications
4
33
2
Order By: Relevance
“…Flow cytometric analysis of peripheral blood immune cells is an established procedure that can be repeated longitudinally in individuals. An altered CD163(+) peripheral blood monocyte level was reported in acute myocardial infarction 38 . Our results showed intriguing differences between normal age‐matched control subjects and AMD patients in the percentages of the CD163(+) cells and serum sCD163.…”
Section: Discussionsupporting
confidence: 56%
“…Flow cytometric analysis of peripheral blood immune cells is an established procedure that can be repeated longitudinally in individuals. An altered CD163(+) peripheral blood monocyte level was reported in acute myocardial infarction 38 . Our results showed intriguing differences between normal age‐matched control subjects and AMD patients in the percentages of the CD163(+) cells and serum sCD163.…”
Section: Discussionsupporting
confidence: 56%
“…These factors could be responsible for the slightly different ROS-induced differentiation patterns observed in both cell types, despite the fact that the treatment varied by a factor of 6 to 12, owing to the increased robustness of THP-1 cells towards ROS-induced cell death [67]. In primary monocytes, the authors observed an increase of CD80 being a stimulatory receptor for T cell activation [68] and CD163, a receptor for the hemoglobin-haptoglobin complex and M2 macrophage marker [68] with plasma treatment. The mannose receptor and M2 macrophage marker CD206 was not changed in plasma treated primary monocytes, partly arguing against such M2 phenotype upon ROS-induced differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…Correlation analysis for aminobutyric acid related genes. Since osteoporosis is a metabolic syndrome, where inflammation plays a major role, and given the relevance of peripheral blood monocytes (PBM) to the pathogenesis of aging-related, inflammatory, and degenerative diseases [27][28][29] , we investigated the gene expression profiles for the aminobutyric acids-related genes from PBMs. PBM information was available from 122 out of 136 young women subjects with high or low BMD (Supplementary Table 7) 30 .…”
Section: Quantification Of Aminobutyric Acids In Biological Fluidsmentioning
confidence: 99%